Contribution of Heat Fluxes on Cyclone Narelle as Simulated by a Mesoscale Model - Yopi Ilhamsyah; Frinsa Lindiasfika; Ahmad Bey; Ichsan Setiawan; Rizwan .; Junaidi M. Affan (Aceh International Journal of Science and Technology, 2013)
Abstract - Heat fluxes from oceanic evaporation particularly latent heat is important to drive the formation and intensification of Cyclone Narelle. The research was carried out by introducing a mesoscale model, namely Weather and Research Forecasting (WRF). One domain with spatial resolution at 10 km was utilized in the model. The model involved significant physical parameters, e.g., Kain-Fritsch in the cumulus scheme, Yonsei University in the Planetary Boundary Layer scheme, and WRF Single-Moment 3-class in the microphysics scheme. The analysis focused on January 8th to 14th upon all stages of Narelle. The result showed that Sea Surface Temperatures (SST) higher than 26°C was a favorable environment for Cylone Narelle to form. Surface sensible and latent heat fluxes have strong positive correlation with wind speed and SST. It can be concluded that these variables were highly correlated with surface heat flux that further lead to the formation and intensification of Cyclone Narelle in early January 2013 over South Indian Ocean. The tracks and stages of the model are nearly similar to the observations, the differences are found in late phases of Narelle.  Keywords: Latent heat; WRF; SST; Sensible heat; Wind speed